Analysis of tropical‐like cyclones over the Mediterranean Sea through a combined modeling and satellite approach. Issue 10 (30th May 2013) - Miglietta, M. M.; Laviola, S.; Malvaldi, A.; Conte, D.; Levizzani, V.; Price, C.
Abstract : [1] Several Mediterranean vortices with characteristics similar to tropical cyclones are analyzed by means of numerical simulations, satellite products and lightning data. Numerical analysis suggests that the broad tropical‐like cyclone category includes in reality a set of different cyclones, ranging from very small and weak vortices to larger and stronger cyclones. One case displays a much longer persistence of tropical features than the other events. The analysis of the tracks identifies two preferred areas of occurrence: the Ionian sea and the Balearic Islands. The satellite analysis of cloud top height and retrieved rainfall indicates that the stage characterized by the most intense convective activity and rainfall anticipates the mature phase, when the cyclone is more intense and characterized by tropical features, during which convection is shallower and rainfall weaker. This result is confirmed by a preliminary analysis of the lightning activity. Key Points: The category of tropical‐like cyclones includes a wide range of vortices A specific case shows a long persistence of tropical features Intense convective activity anticipates the cyclone mature phase